Evaluasi Sistem Penyaliran Tambang Untuk Mendapatkan Sistem Penyaliran Ideal Tahun 2019 di Pit Markona Penambangan Batubara PT. Bumi Karya Makmur Jobsite PT. Cakrawala Dinamika Energi, Desa Air Sebayur, Kecamatan Pinang Raya, Kabupaten Bengkulu Utara - Rido Agustian; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Mining operations that used in pit Markona PT. Bumi Karya makmur jobsite PT. Cakrawala Dinamika Energi is open pit method. This method will cause a large basin to form so that it is very potential to become a water reservoir area. Based on the analysis of rainfall data for 2009-2018, the planned rainfall was 110,726 mm/day, with different rainfall intensity in each catchment area with a return period of 2 years. The problem solving method is carried out by analyzing several alternative solutions related to handling the discharge of water that entering the pit, there are alternative I, recommending a diversion channel that can minimize runoff discharge by 0.258 m3/second. Alternative II, recommendations for optimal sump dimensions to accommodate water discharge with a maximum volume of 38.785 m3. Alternative III, recommendation of pump optimization is 5 units to compensate for the dimensions of the existing sump. Based on this alternative analysis, recommend an effective and efficient alternative in pit Markona 2019 is the recommendation of the diversion channel. The settling pond consists of 3 compartments with capacities of each compartment of 7,096.44 m3, 7,525.68 m3 and 6,821.42 m3.Keywords: Mine Drainage, Catchment Area, Pump, Sump, Open Channel, Settling Pond